Electrolyte, battery, battery assembly and electric device

CN123018136APending Publication Date: 2026-10-30BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510903697.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-30
Filing Date
2025-06-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,随着对快速充电需求以及高温环境下电池性能要求的不断提高,现有锂离子电池的快充性能以及高温存储性能已成为限制其进一步应用的重要瓶颈

Benefits of technology

[0015]本申请第二方面提供一种电池,通过利用根据本申请的第一方面所述的电解液,该电池具有良好的快充性能,同时具有良好的高温存储性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an electrolyte, which comprises a carbonate solvent, a nitrate and a lithium boron-containing oxalate salt, the mass ratio of the nitrate in the electrolyte is x, the mass ratio of the lithium boron-containing oxalate salt in the electrolyte is y, and 0 < y < x <= 1%. The battery prepared from the electrolyte can guarantee high-temperature storage performance on the basis of taking into account fast charging performance, and effectively improves the defects of the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to an electrolyte, a battery, a battery assembly, and an electrical device. Background Technology

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and low self-discharge rate. However, with the increasing demand for fast charging and high-temperature performance requirements, the fast-charging performance and high-temperature storage performance of existing lithium-ion batteries have become significant bottlenecks limiting their further application. Summary of the Invention

[0003] This application aims to at least address one of the technical problems existing in the prior art. Therefore, one object of the present invention is to provide an electrolyte that enables batteries prepared with this electrolyte to maintain both fast-charging performance and high-temperature storage performance, thereby effectively improving the deficiencies of the prior art.

[0004] According to a first aspect of this application, an electrolyte is provided, comprising a carbonate solvent, a nitrate, and a boron-containing lithium oxalate salt, wherein the mass ratio of the nitrate to the electrolyte is x, and the mass ratio of the boron-containing lithium oxalate salt to the electrolyte is y, wherein 0 < y < x ≤ 1%.

[0005] The electrolyte provided in this application uses a carbonate solvent, and introduces nitrate and boron-containing lithium oxalate into the carbonate solvent system. The mass ratio x of nitrate and the mass ratio y of boron-containing lithium oxalate in the electrolyte are synergistically controlled to satisfy 0 < y < x ≤ 1%. The nitrate introduced into the carbonate-containing electrolyte in this application can promote the formation of Li3N-rich and nitrogen-containing oxide (LiNO3)-rich compounds on the negative electrode surface. x SEI films, such as those for LiNO2, exhibit high Li content. +While improved electrical conductivity reduces impedance and enhances fast-charging performance, introducing nitrates into the electrolyte, compared to electrolyte systems without nitrates under the same conditions, significantly degrades high-temperature storage performance, although it improves fast-charging performance. Extensive experimental research revealed that this is likely due to the introduction of additional moisture during nitrate addition, which exacerbates lithium salt (especially LiPF6) hydrolysis at high temperatures, generating large amounts of HF. This leads to the dissolution of transition metal ions at the positive electrode and a decrease in battery capacity. Further research showed that introducing boron-containing lithium oxalate into the nitrate-containing electrolyte system significantly improves the battery's capacity retention after high-temperature storage. This is likely because boron-containing lithium oxalate reacts with HF acid, acting as an acid remover and inhibiting HF corrosion of the positive electrode, thereby increasing battery capacity. This solves the high-temperature storage performance problem caused by nitrates and ensures the high-temperature storage performance of the battery system. In addition, this scheme controls the mass content of boron oxalate lithium salt to be lower than that of nitrate, while controlling the mass content of nitrate to be less than or equal to 1%. This can prevent the formation of an SEI film with excessively high impedance on the negative electrode surface by boron oxalate lithium salt, improve the high-temperature storage performance of batteries made with electrolytes containing nitrate, and reduce the impact of boron oxalate lithium salt on the battery's internal resistance, thus ensuring the battery's fast-charging performance.

[0006] According to some embodiments of this application, 0 < x ≤ 0.9%.

[0007] According to some embodiments of this application, 0 < x ≤ 0.5%.

[0008] According to some embodiments of this application, the boron-containing lithium oxalate salt includes at least one of lithium bis(oxalate-borate) and lithium difluorooxalate-borate.

[0009] According to some embodiments of this application, the nitrate includes lithium nitrate.

[0010] According to some embodiments of this application, the carbonate solvent accounts for more than or equal to 80% of the mass of the electrolyte.

[0011] According to some embodiments of this application, the carbonate solvent includes at least one of ethylene carbonate, methyl ethyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, butene carbonate, methyl propyl carbonate, and ethyl propyl carbonate.

[0012] According to some embodiments of this application, the electrolyte further includes a main lithium salt, which includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, and lithium difluorophosphate. The mass ratio of the main lithium salt to the electrolyte is z, where 10% ≤ z ≤ 18%.

[0013] According to some embodiments of this application, the electrolyte further includes at least one of a co-solvent and a film-forming additive. The co-solvent includes at least one of a sulfone solvent, an ether solvent, and an ionic co-solvent. Preferably, the sulfone solvent includes at least one of dimethyl sulfoxide, sulfolane, tetramethylene sulfolane, dimethyl sulfone, dibutyl sulfone, dipropyl sulfone, diethyl sulfone, benzyl sulfone, diphenyl sulfone, ethylmethyl sulfone, ethylphenyl sulfone, benzyl sulfone, methoxyethylmethyl sulfone, ethylmethoxyethyl sulfone, and ethylmethoxyethoxyethyl sulfone. The agent includes at least one of ethylene glycol dimethyl ether, ethylene glycol methyl ethyl ether, ethylene glycol diethyl ether, 1,4-butanediol dimethyl ether, 1,4-butanediol diethyl ether, and 1,4-butanediol methyl ethyl ether; the ionic co-solvent includes at least one of lithium trifluoromethanesulfonate, tin trifluoromethanesulfonate, copper fluoride, potassium salt, magnesium salt, cesium salt, aluminum salt, indium salt, silver salt, zinc salt, and tetraethylammonium nitrate; and the film-forming additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, methanedisulfonate, and siloxane additives.

[0014] According to some embodiments of this application, the mass ratio of the cosolvent to the electrolyte is m, where 0 < m ≤ 4%, preferably 0.1% ≤ m ≤ 1.5%; the mass ratio of the film-forming additive to the electrolyte is n, where 0 < n ≤ 5%, preferably 0.5% ≤ n ≤ 3%.

[0015] The second aspect of this application provides a battery that, by utilizing the electrolyte described in the first aspect of this application, has good fast-charging performance and good high-temperature storage performance.

[0016] A third aspect of this application provides a battery assembly that, by utilizing the battery described in the second aspect of this application, has good fast-charging performance and good high-temperature storage performance.

[0017] The fourth aspect of this application provides an electrical device that, by utilizing the battery according to the second aspect of this application or the battery assembly described in the third aspect, has good fast charging performance and good high-temperature storage performance. Detailed Implementation

[0018] To make the technical problems, technical solutions, and beneficial effects solved by this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are exemplary and used to explain the invention, and should not be construed as limiting the invention.

[0019] This application is based on the inventor's discovery and understanding of the following facts and problems: According to the inventor's research, a battery typically includes a cell and an electrolyte that wets the cell. The cell includes a positive electrode, a negative electrode, and a separator between the positive and negative electrodes. During the charging and discharging process of the battery, active ions (such as lithium ions in a lithium-ion battery) are transported between the positive and negative electrodes through the electrolyte and undergo corresponding extraction / intercalation. During the charging and discharging process, solvents, additives, and lithium salts in the electrolyte undergo a reduction reaction on the surface of the negative electrode, generating an SEI film (solid electrolyte interphase). The SEI film conducts ions but not electrons, which can inhibit further reduction and consumption of the electrolyte. However, the SEI film formed by carbonate electrolytes has poor ionic conductivity, hindering the absorption of lithium ions (Li). + The insertion / extraction process of active ions such as lithium phosphate (LiNO3) affects the fast-charging performance of batteries. According to the inventors' research, using carbonate solvents and adding nitrates (such as lithium nitrate (LiNO3)) to the electrolyte can form an SEI film with high ionic conductivity, improving the battery's fast-charging performance. However, the introduction of additional moisture during the nitrate process can exacerbate the hydrolysis of lithium salts (especially LiPF6) under high-temperature conditions, generating a large amount of HF. This leads to the dissolution of transition metal ions at the positive electrode, a decrease in battery capacity, and affects the performance of electrode materials, thus impacting the battery's high-temperature storage performance. How to improve battery performance while avoiding these problems, thereby simultaneously improving both fast charging and cycle stability, remains a challenge that needs to be overcome.

[0020] In view of this, a first aspect of this application provides an electrolyte comprising a carbonate solvent, a nitrate, and a boron-containing lithium oxalate salt, wherein the nitrate accounts for x of the mass ratio of the electrolyte, and the boron-containing lithium oxalate salt accounts for y of the mass ratio of the electrolyte, wherein 0 < y < x ≤ 1%.

[0021] The electrolyte provided in this application uses a carbonate solvent, and introduces nitrate and boron-containing lithium oxalate into the carbonate solvent system. The mass ratio x of nitrate and the mass ratio y of boron-containing lithium oxalate in the electrolyte are synergistically controlled to satisfy 0 < y < x ≤ 1%. The nitrate introduced into the carbonate-containing electrolyte in this application can promote the formation of Li3N-rich and nitrogen-containing oxide (LiNO3)-rich compounds on the negative electrode surface. x SEI films, such as those for LiNO2, exhibit high Li content. +Electrical conductivity is beneficial for reducing impedance and improving the fast-charging performance of batteries. However, while introducing nitrates into the electrolyte improves the fast-charging performance of the assembled battery compared to an electrolyte system without nitrates under the same conditions, it significantly degrades the high-temperature storage performance. Through extensive experimental research, the inventors discovered that this may be due to the additional water easily introduced during the process of introducing nitrates into the electrolyte. On the one hand, the nitrates used in the electrolyte formulation may themselves carry a certain amount of water due to factors such as the preparation process or the water absorption of materials. On the other hand, the co-solvents commonly used to promote the dissolution of nitrates in carbonate electrolytes also contain a certain amount of water. The presence of water also promotes the dissolution of nitrates. Furthermore, according to the principle of "like dissolves like," the co-solvents and water molecules have good compatibility, making complete water removal difficult. The introduction of nitrates into the electrolyte inevitably introduces additional moisture, which, under high-temperature conditions, exacerbates the hydrolysis of lithium salts (especially LiPF6), generating large amounts of HF. This leads to the dissolution of transition metal ions at the positive electrode, resulting in a decrease in battery capacity. Further research by the inventors revealed that introducing boron-containing lithium oxalate into an electrolyte system containing nitrates significantly improves the battery's capacity retention after high-temperature storage. The reason for this is likely that boron-containing lithium oxalate reacts with HF acid, acting as an acid remover and inhibiting HF corrosion of the positive electrode, thereby increasing battery capacity. This solves the high-temperature storage performance problem caused by nitrates and ensures the high-temperature storage performance of the battery system. Furthermore, the film-forming potentials of boron-containing lithium oxalate and nitrates are relatively close. Excessive addition of boron-containing lithium oxalate may compete with nitrates for film formation on the negative electrode surface, thus weakening the film-forming effect of nitrates and making it difficult to form high-Li... + The high conductivity of the SEI film can actually lead to an excessively thick SEI film, increasing the battery's internal resistance and affecting its fast-charging performance. This solution controls the mass content of boron oxalate to be lower than that of nitrate, while also controlling the nitrate mass content to be less than or equal to 1%. This avoids the formation of an excessively high-resistivity SEI film on the negative electrode surface by the boron oxalate, improving the high-temperature storage performance of batteries made with nitrate-containing electrolytes, while reducing the impact of boron oxalate on the battery's internal resistance and ensuring the battery's fast-charging performance.

[0022] According to the embodiments of the present application, x is, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, or a range formed by any two thereof. y is, for example, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, or a range formed by any two thereof.

[0023] According to the embodiments of the present application, 0<x≤0.9%. x is, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, or a range formed by any two thereof. By further controlling the content x of the nitrate in the electrolyte within this range, it is beneficial to promote the dissolution of the nitrate while further avoiding the introduction of extra moisture, which is more conducive to simultaneously improving the fast charging performance and high-temperature storage performance of the battery. At the same time, further controlling the content y of the boron-containing lithium oxalate salt in the electrolyte within this range further prevents the boron-containing lithium oxalate salt from forming an SEI film with excessively high impedance on the negative electrode surface, improves the high-temperature storage performance of the battery prepared with the nitrate-containing electrolyte, and reduces the influence of the boron-containing lithium oxalate salt on the internal resistance of the battery, further ensuring the fast charging performance of the battery.

[0024] According to the embodiments of the present application, 0<x≤0.5%. By further adjusting the amount of the nitrate in the electrolyte to meet the above range, it is beneficial to its dissolution in the electrolyte, and an SEI film with high ionic conductivity and stability is formed on the electrode surface, which is more conducive to simultaneously improving the fast charging performance and high-temperature storage performance of the battery.

[0025] According to the embodiments of the present application, the boron-containing lithium oxalate salt includes at least one selected from lithium bis(oxalate)borate (LiBOB) and lithium difluoro(oxalate)borate (LiDFOB). The above-mentioned boron-containing lithium oxalate salt can react with HF acid, acting as an acid remover, and inhibiting the corrosion of the positive electrode by HF. Especially in the ether-based co-solvent system, the boron-containing lithium oxalate salt forms a solid electrolyte interphase on the surface of the positive electrode, which is also beneficial to inhibiting the oxidative decomposition of the ether-based electrolyte, thus ensuring the high-temperature storage performance of the battery system.

[0026] According to the embodiments of this application, the nitrate may include lithium nitrate, which can reduce the decomposition of carbonate solvents, reduce battery gas production, improve battery cycle life, and is more conducive to synergistic effect with boron-containing lithium oxalate. In the above electrolyte, in the coexistence system of lithium nitrate and boron-containing lithium oxalate, when the electrolyte is applied to lithium-ion batteries, it is more conducive to forming an SEI film with high lithium-ion conductivity and stability on the electrode surface, thus improving both the fast charging performance and high-temperature cycle stability of lithium-ion batteries.

[0027] According to the embodiments of this application, the carbonate solvent accounts for 80% or more of the electrolyte by mass, for example, 85%, 90%, 95%, or any combination thereof. The electrolyte is predominantly carbonate solvent, meaning it is a carbonate-based electrolyte. Introducing the aforementioned proportions of nitrate and boron-containing lithium oxalate salts into it helps to improve both the fast-charging and high-temperature storage performance of the battery. Simultaneously, it also facilitates electrolyte preparation, offering advantages such as low production costs and greater suitability for practical industrial applications.

[0028] According to embodiments of this application, the carbonate solvent may include at least one of ethylene carbonate, methyl ethyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, butene carbonate, methyl propyl carbonate, and ethyl propyl carbonate. This facilitates better dissolution of nitrates in carbonate solvents and promotes the formation of a high-ionic-conductivity and stable SEI film on the electrode surface, thereby improving both the fast-charging and high-temperature cycling stability of the battery.

[0029] According to embodiments of this application, the electrolyte may further include a main lithium salt, which may include at least one of lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), lithium bis(trifluoromethanesulfonylimide) (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), and lithium difluorophosphate (LiPO2F2). The mass ratio of the main lithium salt to the electrolyte is z, where 10% ≤ z ≤ 18%, for example, z can be a range of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, or any two of these. This is beneficial for further improving the wetting ability and ion diffusion rate of the electrolyte, reducing the battery internal resistance, and improving the battery's cycle life and other performance characteristics.

[0030] According to embodiments of this application, the electrolyte further includes at least one of a co-solvent and a film-forming additive, wherein the co-solvent includes at least one of a sulfone solvent, an ether solvent, and an ionic co-solvent. By introducing at least one of a sulfone solvent, an ether solvent, and an ionic co-solvent into the electrolyte, the dissolution of nitrates in the carbonate-based electrolyte can be promoted. When the electrolyte is applied to lithium-ion batteries, it is more conducive to forming an SEI film with high lithium-ion conductivity and stability on the electrode surface, thus improving both the fast-charging performance and high-temperature cycle stability of the lithium-ion battery. Introducing a film-forming additive into the electrolyte facilitates the formation of an additional SEI film on the negative electrode surface, improving the density and integrity of the SEI film and ensuring battery performance.

[0031] According to embodiments of this application, sulfone solvents include at least one of dimethyl sulfoxide, sulfolane, tetramethylene sulfolane, dimethyl sulfone, dibutyl sulfone, dipropyl sulfone, diethyl sulfone, benzyl sulfone, diphenyl sulfone, ethyl methyl sulfone, ethyl phenyl sulfone, benzosulfone, methoxyethyl methyl sulfone, ethyl methoxyethyl sulfone, and ethyl methoxyethoxyethyl sulfone; ether solvents include at least one of ethylene glycol dimethyl ether, ethylene glycol methyl ethyl ether, ethylene glycol diethyl ether, 1,4-butanediol dimethyl ether, 1,4-butanediol diethyl ether, and 1,4-butanediol methyl ethyl ether; and ionic co-solvents include at least one of lithium trifluoromethanesulfonate, tin trifluoromethanesulfonate, copper fluoride, potassium salt, magnesium salt, cesium salt, aluminum salt, indium salt, silver salt, zinc salt, and tetraethylammonium nitrate. By introducing at least one of sulfone solvents, ether solvents, and ionic co-solvents into the electrolyte, the solubility of nitrates in carbonate-based electrolytes can be promoted, further improving the solubility of nitrates in the electrolyte. When the electrolyte is applied to lithium-ion batteries, it is more conducive to the formation of an SEI film with high lithium-ion conductivity and stability on the electrode surface. At the same time, it can also reduce the co-intercalation reaction between electrolyte components and graphite, thus improving both the fast-charging performance and high-temperature cycle stability of lithium-ion batteries.

[0032] According to the embodiments of this application, the co-solvent includes an ether-based co-solvent. The ether-based co-solvent can better promote the dissolution of nitrate in the carbonate solvent system electrolyte. The nitrate dissolved in the electrolyte can act as a film-forming agent to form a high ionic conductivity SEI film on the electrode surface. At the same time, the formation of the SEI film on the electrode surface can also prevent the co-intercalation reaction of components such as the ether-based co-solvent in the electrolyte in the graphite, effectively suppressing the co-intercalation reaction of the ether-based co-solvent on the graphite negative electrode under fast charging and high temperature conditions, thereby improving the cycle stability of the battery under fast charging and high temperature conditions.

[0033] According to embodiments of this application, the film-forming additive includes at least one selected from vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, methylene disulfonate, and siloxane additives. Introducing the film-forming additive into the electrolyte facilitates the formation of an SEI film on the negative electrode surface. Based on components such as nitrates and boron-containing lithium oxalate, this further improves the ionic conductivity and stability of the SEI film, thereby enhancing both the battery's fast-charging performance and high-temperature storage performance.

[0034] According to embodiments of this application, the mass ratio of the co-solvent to the electrolyte is m, where 0 < m ≤ 4%, for example, m can be a range of 0.5%, 1%, 2%, 3%, 3.5%, or any two of these. The mass ratio of the film-forming additive to the electrolyte is n, where 0 < n ≤ 5%, for example, n can be a range of 0.5%, 1%, 2%, 3%, 4%, or any two of these.

[0035] According to the embodiments of this application, 0.1% ≤ m ≤ 1.5%, for example, m can be a range of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, or any two of these. 0.5% ≤ n ≤ 3%. For example, n can be a range of 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, 2.0%, 2.3%, 2.6%, 3.0%, or any two of these.

[0036] A second aspect of this application also provides a battery including the electrolyte described above, which has advantages corresponding to the electrolyte described above, which will not be elaborated further.

[0037] According to an embodiment of this application, the battery includes a cell and a casing for encapsulating the cell. Electrolyte is injected into the cell within the casing. The cell includes a positive electrode, a negative electrode, and a separator located between the positive and negative electrodes. The cell can be a stacked cell, meaning it is formed by alternating layers of positive electrode, separator, and negative electrode. Alternatively, it can be a wound cell, meaning it is formed by stacking positive electrode, negative electrode, and separator and then winding them.

[0038] According to an embodiment of this application, the positive electrode sheet includes a positive current collector and a positive electrode coating located on at least one side of the positive current collector. Specifically, the positive electrode coating may be provided on one side of the positive current collector, or positive electrode coatings may be provided on both opposite sides in the thickness direction of the positive current collector.

[0039] According to embodiments of this application, the positive electrode coating (positive electrode active material layer) may include a positive electrode active material, a conductive agent, and a binder, all of which can be conventional materials in the art. For example, the positive electrode active material may include one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and ternary cathode materials. The ternary cathode materials may include nickel-cobalt-manganese ternary materials and / or nickel-cobalt-aluminum ternary materials. The conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fiber. The binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyethylene, polypropylene, polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, etc.

[0040] According to embodiments of this application, the positive current collector can be a metal current collector or a composite current collector. For example, metal current collectors include, but are not limited to, aluminum foil current collectors; composite current collectors may include a polymer material base layer (such as a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) and a metal layer (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) formed on at least one surface of the polymer material base film.

[0041] According to embodiments of this application, the positive electrode adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a terpolymer of PVDF-tetrafluoroethylene-propylene, a terpolymer of PVDF-hexafluoropropylene-tetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorinated acrylate resin. This allows for better adhesion of the positive electrode active material to the positive electrode current collector, resulting in stronger adhesion and reducing the likelihood of problems such as positive electrode dressing detachment.

[0042] According to embodiments of this application, the positive electrode conductive agent may include at least one selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon nanotubes, graphene, and carbon nanofibers. This effectively improves conductivity, reduces internal resistance, and enhances the electrochemical performance of lithium-ion batteries.

[0043] According to the embodiments of this application, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the positive electrode active material, conductive agent, binder, and other components used to form the positive electrode coating can be dispersed in a positive electrode solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry. This slurry is then coated onto the surface of the positive electrode current collector, and after drying, rolling, and other processes, the positive electrode sheet is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing positive electrode sheets using the coating method, and are not particularly limited thereto.

[0044] According to an embodiment of this application, the negative electrode sheet includes a negative electrode current collector and a negative electrode coating located on at least one side surface of the negative electrode current collector. Specifically, the negative electrode coating may be provided on one side surface of the negative electrode current collector, or negative electrode coatings may be provided on both opposite sides of the negative electrode current collector in the thickness direction.

[0045] According to embodiments of this application, the negative electrode coating (negative electrode active material layer) may include a negative electrode active material (negative electrode active material), a conductive agent, and a binder, all of which can be conventional materials in the art. For example, the negative electrode active material may include one or more of graphite, silicon, silicon oxide, and lithium metal; the conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber; the binder may include one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0046] According to the embodiments of this application, the negative electrode active material includes graphite. By using the above-mentioned electrolyte, it is beneficial to form an SEI film with high ionic conductivity and stability on the surface of the graphite negative electrode, thereby improving the battery's fast charging cycle stability and high temperature cycle stability. Moreover, graphite has high industrial maturity, low cost, and strong compatibility with the positive electrode, making it suitable for large-scale production.

[0047] According to embodiments of this application, the negative electrode current collector can be a metal current collector or a composite current collector. For example, metal current collectors include, but are not limited to, copper foil current collectors; composite current collectors may include a polymer material base layer (such as a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) and a metal layer (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) formed on at least one surface of the polymer material base layer.

[0048] According to embodiments of this application, the negative electrode binder may include, but is not limited to, at least one of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0049] According to embodiments of this application, the negative electrode conductive agent may include, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon nanotubes, graphene, and carbon nanofibers.

[0050] According to the embodiments of this application, the negative electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the components used to form the negative electrode coating, such as the negative electrode active material, conductive agent, and binder, can be dispersed in a negative electrode solvent, such as water, to prepare a negative electrode slurry. This slurry is then coated onto the surface of the negative electrode current collector, and after drying, rolling, and other processes, the negative electrode sheet is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing negative electrode sheets using the coating method, and are not particularly limited thereto.

[0051] According to the embodiments of this application, the separator is used to separate the positive electrode and the negative electrode to avoid short circuit between the positive electrode and the negative electrode. The embodiments of the present invention may use conventional separators in the art, such as polypropylene membranes (PP membranes), but are not limited thereto.

[0052] According to the embodiments of this application, the battery cell can be packaged using conventional housing materials in the art, such as aluminum-plastic film and other soft packaging materials (in which case the battery is a soft-pack battery), but is not limited to this.

[0053] According to the embodiments of this application, components such as positive electrode, separator and negative electrode can be assembled into a battery by conventional methods in the art. For example, positive electrode, separator and negative electrode can be stacked in an alternating manner to obtain a stacked cell (or wound into a wound cell); then the cell is placed in a casing and subjected to conventional processes such as electrolyte injection (i.e., injection of electrolyte) and formation to obtain a battery.

[0054] The third aspect of this application provides a battery assembly that, by utilizing the battery according to the second aspect of this application, has good fast-charging performance and good high-temperature storage performance.

[0055] According to embodiments of this application, the specific type of battery assembly is not particularly limited; the battery assembly can be a battery module, a battery pack, etc. In some embodiments, the batteries can be assembled into a battery module, and the number of batteries contained in the battery module can be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery module. In some embodiments, the batteries can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery pack.

[0056] The fourth aspect of this application provides an electrical device that, by utilizing the battery according to the second aspect of this application or the battery assembly described in the third aspect of this application, has good fast charging performance and good high-temperature storage performance.

[0057] According to the embodiments of this application, the specific type of electrical equipment is not particularly limited, and it can be any device that uses a lithium-ion battery as a power source or energy storage unit. As examples, electrical equipment includes, but is not limited to, electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (e.g., mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, etc.

[0058] It is understandable that, in addition to the battery mentioned above, the electrical device also includes other necessary structures and components, all of which can be made with reference to conventional technologies. For example, an electric vehicle may include a body, chassis, tires, navigation system, radar system, steering system, braking system, lubrication system, cooling system, driving system, etc., which will not be described in detail here.

[0059] According to the embodiments of this application, ion chromatography (IC) and gas chromatography-mass spectrometry (GC-MS) can be used to detect the components and their contents in the electrolyte, such as nitrates, boron-containing lithium oxalate, and organic solvents. For example, the contents of nitrates and boron-containing lithium oxalate in the electrolyte can be measured by IC, and the contents of organic solvents can be measured by GC-MS.

[0060] For example, the nitrate content in the electrolyte can be tested using an ion chromatograph (IC). Taking the IC-2800 ion chromatograph as an example, the test conditions are as follows: anion exchange column, suppressor current 35 mA, flow rate 1 mL / min, eluent 5 mmol / L sodium carbonate solution: acetone = 75:25, injection volume 100 µL; the test process is as follows: (1) First, dilute the sample to be tested: take 1 mL of electrolyte, dilute with acetonitrile and transfer to a 100 mL volumetric flask, dilute to the mark with acetonitrile, shake well and test; (2) Next, prepare the standard solution: take 0.05 mL of NO3 with a concentration of 1 mg / mL. - An aqueous solution (prepared using a nitrate such as lithium nitrate) is diluted to a final volume of 10 mL with deionized water to obtain NO3 with a concentration of 5 µg / mL. - Aqueous solution: Take 1 mL, 2 mL, 4 mL, and 10 mL of the solution into a 10 mL volumetric flask, and dilute to the mark with deionized water to prepare a series of standard solutions with concentration gradients; (3) Analyze the standard sample: with NO3 - The peak area (y) is used as the vertical axis and the concentration of the standard sample is used as the horizontal axis (x). A standard curve is established, and the curve equation and correlation coefficient are obtained. (4) Finally, the electrolyte to be tested is tested, and the measured NO3 is used as the standard curve. -Substituting the peak area into the standard curve equation, the nitrate (such as lithium nitrate) content in the electrolyte can be calculated. The test for boron-containing lithium oxalate content is similar to that for nitrates and will not be elaborated here. Example

[0061] Positive electrode preparation: Polyvinylidene fluoride (binder) is added to N-methylpyrrolidone (solvent) and stirred to dissolve. Then, conductive carbon black (conductive agent) and lithium iron phosphate (positive electrode active material) are added and kneaded thoroughly to obtain a positive electrode slurry (lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride in a weight ratio of 8:1:1). The above positive electrode slurry is uniformly coated on current collector aluminum foil, and after baking and rolling, a positive electrode sheet is obtained.

[0062] Negative electrode preparation: Graphite (negative electrode active material), conductive carbon black (conductive agent), SBR (binder), and CMC (thickener) are mixed in a mass ratio of 8:1:0.5:0.5. Deionized water is added as a solvent and the mixture is kneaded thoroughly to obtain a negative electrode slurry. The negative electrode slurry is uniformly coated onto a current collector copper foil and then baked and rolled to obtain a negative electrode sheet.

[0063] Electrolyte: The electrolyte is prepared by uniformly mixing 0.25 wt% lithium nitrate (LiNO3), 0.78 wt% dimethyl ethylene glycol (DME), 0.1 wt% lithium bis(oxalato)borate (LiBOB), 84.32 wt% carbonate solvent (EC / DMC volume ratio 1:1), 2 wt% vinylene carbonate (VC), and 12.55 wt% lithium hexafluorophosphate (LiPF6).

[0064] Separator: A commercially available PE copolymer microporous membrane with a thickness of 11μm is used. Assembly: Positive electrode, separator and negative electrode are alternately stacked to form a stacked cell; the cell is encapsulated with aluminum-plastic film and electrolyte is injected into it, and then the battery is obtained after formation and other processes.

[0065] The preparation of Examples 2-12 and Comparative Examples 1-5 was basically the same as that of Example 1, with the differences shown in Table 1.

[0066] Table 1 sample x(%) Boron oxalate y(%) Cosolvent m(%) <![CDATA[W 碳酸酯类溶剂 (%)]]> n(%) z(%) Example 1 0.25 LiBOB 0.1 DME 0.78 84.32 2 12.55 Example 2 0.25 LiBOB 0.2 DME 0.78 84.22 2 12.55 Example 3 0.35 LiBOB 0.3 DME 1.1 83.7 2 12.55 Example 4 0.45 LiBOB 0.4 DME 1.4 83.2 2 12.55 Example 5 0.5 LiBOB 0.45 DME 1.6 82.9 2 12.55 Example 6 1 LiBOB 0.95 DME 3.2 80.3 2 12.55 Example 7 0.25 LiBOB 0.2 DMSO 1 84 2 12.55 Example 8 0.1 LiBOB 0.05 DME 0.54 84.76 2 12.55 Example 9 0.8 LiBOB 0.7 DME 2.3 81.65 2 12.55 Example 10 0.25 LiDFOB 0.1 DME 0.78 84.32 2 12.55 Example 11 0.35 LiBOB 0.3 DME 1.1 83.7 4 10.55 Example 12 0.35 LiBOB 0.3 DME 1.1 81.7 2 14.55 Comparative Example 1 / / / / 85.45 2 12.55 Comparative Example 2 0.25 / DME 0.78 84.42 2 12.55 Comparative Example 3 0.25 LiBOB 0.5 DME 0.78 83.92 2 12.55 Comparative Example 4 1.5 / DMSO 6 77.95 2 12.55 Comparative Example 5 / LiBOB 0.5 / / 84.95 2 12.55 Performance testing: The performance of the lithium-ion batteries in each embodiment and comparative example was tested using the following process, and the results are shown in Table 1: 1. Fast charging performance test: At room temperature, perform constant current charging to 3.8 V at 1 C and then constant current discharging to 2 V at 1 C to complete a constant current charge-discharge test, and obtain the discharge capacity of the 1 C constant current charge-discharge test; then perform constant current charging to 3.8 V at 5 C and then constant current discharging to 2 V at 5 C to complete a constant current charge-discharge test, and obtain the discharge capacity of the 5 C constant current charge-discharge test, where the percentage of the discharge capacity of the 5 C constant current charge-discharge test relative to the discharge capacity of the 1 C constant current charge-discharge test is the capacity retention rate R 快充 .

[0067] 2. High-temperature cycle stability test: At room temperature, perform constant current charging to 3.8 V at 0.33 C and record this charging capacity, transfer the battery to an oven at 60 °C for 7 days of storage, take out the battery cell, perform constant current charging to 3.8 V at 0.33 C, then perform constant current discharging to 2 V at 0.33 C for constant current charge-discharge, and cycle for 5 turns; repeat the above process of 60 °C oven storage and constant current charge-discharge cycle 3 times, test the capacity of the battery after the last 5 cycles, and calculate the ratio of this battery capacity to the charging capacity before the first storage, that is, the capacity recovery rate R 恢复 .

[0068] The performance test results of each example and comparative example are shown in Table 2: Table 2 sample R Fast Charging R recovery Example 1 66.10% 92.70% Example 2 65.20% 92.60% Example 3 66.00% 92.30% Example 4 67.10% 92.50% Example 5 67.30% 92.10% Example 6 63.20% 90.60% Example 7 64.90% 93.50% Example 8 64.20% 93.30% Example 9 64.00% 91.53% Example 10 66.30% 92.55% Example 11 65.40% 93.30% Example 12 66.20% 92.30% Comparative Example 1 54.00% 91.70% Comparative Example 2 58.10% 85.10% Comparative Example 3 51.50% 93.30% Comparative Example 4 Precipitate precipitates Precipitate precipitates Comparative Example 5 46.20% 95.50% As shown in Table 2, in Examples 1-12 of the present application, by using a carbonate-based solvent electrolyte, doping lithium nitrate and a boron-containing lithium oxalate salt therein at the same time, and controlling the mass content y of the boron-containing lithium oxalate salt to be lower than the mass content x of the nitrate, both fast charging performance and high-temperature storage performance can be achieved. Comparative Example 1 is an electrolyte without added nitrate and boron-containing lithium oxalate salt, and it can be seen that its fast charging performance is poor. Comparative Example 2 is an electrolyte without added boron-containing lithium oxalate salt, and both its fast charging performance and high-temperature storage performance are poor. In Comparative Example 3, the added amount of the boron-containing lithium oxalate salt is more than that of the nitrate, and its fast charging performance is poor. In Comparative Example 4, the added amount of LiNO₃ is excessively high, which causes it to precipitate out in the carbonate electrolyte, failing to form a clear solution. Comparative Example 5 is an electrolyte without added nitrate, and its fast charging performance is poor. In summary, when the mass ratio x of the nitrate in the electrolyte to the electrolyte and the mass ratio y of the boron-containing lithium oxalate salt to the electrolyte satisfy 0 < y < x ≤ 1%, the battery has both good fast charging performance and good high-temperature storage performance.

[0069] In the description of this specification, the references to terms such as "implementation," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0070] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. An electrolyte, characterized in that, The electrolyte includes carbonate solvents, nitrates, and boron-containing lithium oxalate, wherein the mass ratio of the nitrate to the electrolyte is x, and the mass ratio of the boron-containing lithium oxalate to the electrolyte is y, where 0 < y < x ≤ 1%.

2. The battery according to claim 1, characterized in that, 0<x ≤ 0.9%。 3. The battery according to claim 1, characterized in that, 0<x ≤ 0.5%。 4. The battery according to claim 1, characterized in that, The boron-containing lithium oxalate salt includes at least one of lithium bis(oxalate)borate and lithium difluorooxalateborate.

5. The battery according to claim 1, characterized in that, The nitrates include lithium nitrate.

6. The battery according to any one of claims 1-5, characterized in that, The carbonate solvent accounts for 80% or more of the mass of the electrolyte.

7. The battery according to claim 6, characterized in that, The carbonate solvents include at least one of ethylene carbonate, methyl ethyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate, butene carbonate, methyl propyl carbonate, and ethyl propyl carbonate.

8. The battery according to any one of claims 1-5, characterized in that, The electrolyte further includes a main lithium salt, which includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, and lithium difluorophosphate. The main lithium salt accounts for z of the electrolyte by mass, where 10% ≤ z ≤ 18%.

9. The battery according to any one of claims 1-5, characterized in that, The electrolyte further includes at least one of a co-solvent and a film-forming additive, wherein the co-solvent includes at least one of a sulfone solvent, an ether solvent, and an ionic co-solvent. Preferably, the sulfone solvent includes at least one selected from dimethyl sulfoxide, sulfolane, tetramethylene sulfolane, dimethyl sulfone, dibutyl sulfone, dipropyl sulfone, diethyl sulfone, benzyl sulfone, diphenyl sulfone, ethyl methyl sulfone, ethyl phenyl sulfone, sulfone benzyl sulfone, methoxyethyl methyl sulfone, ethyl methoxyethyl sulfone, and ethyl methoxyethoxyethyl sulfone. The ether solvent includes at least one selected from ethylene glycol dimethyl ether, ethylene glycol methyl ethyl ether, ethylene glycol diethyl ether, 1,4-butanediol dimethyl ether, 1,4-butanediol diethyl ether, and 1,4-butanediol methyl ethyl ether. The ionic co-solvent includes at least one of lithium trifluoromethanesulfonate, tin trifluoromethanesulfonate, copper fluoride, potassium salt, magnesium salt, cesium salt, aluminum salt, indium salt, silver salt, zinc salt, and tetraethylammonium nitrate. The film-forming additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, methane disulfonate, and siloxane additives.

10. The battery according to claim 9, characterized in that, The mass ratio of the co-solvent to the electrolyte is m, where 0 < m ≤ 4%, preferably 0.1% ≤ m ≤ 1.5%. The film-forming additive accounts for n% of the electrolyte by mass, where 0 < n ≤ 5%, preferably 0.5% ≤ n ≤ 3%.

11. A battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte as described in any one of claims 1-10.

12. A battery assembly, characterized in that, It includes at least two batteries as described in claim 11.

13. An electrical appliance, characterized in that, The electrical device includes an electrical appliance and the battery of claim 11 or the battery assembly of claim 12, wherein the battery or the battery assembly is used to supply power to the electrical appliance.